Collaborative Concept Mapping: A Study of Group Work Satisfaction in Vocational Higher Education - Malikhatul Lailiyah; Karlina Karadila Yustisia (Journal of Vocational Education Studies, 2022)
Collaboration is gaining traction in today's educational environment. Thus, teachers' primary concern is assisting students in experiencing group knowledge collaboration. As online education continues to grow in popularity, there is an increasing need to promote and understand collaborative learning processes. Its success is contingent upon implementing online collaborative learning strategies that foster critical thinking abilities while also providing meaningful collaborative learning opportunities. Collaborative concept mapping is one tool that could be used to foster student collaboration. Rather than creating and visualizing ideas individually, collaborative concept mapping involves two or more students working collaboratively to create one or more concept maps. In collaborative learning, interactions between learners are critical sources of idea generation. The purpose of this study is to examine students’ satisfaction with implementing the strategy in Second Language Reading class. The recent study advances our understanding of how to effectively use collaborative teaching tools in the classroom and improve student learning through group collaboration. The study's findings indicate that students demonstrated positive attitudes toward group collaboration, as evidenced by collaborative concept mapping. In addition, the collaborative learning processes embedded in concept mapping learning platforms support and facilitate reading comprehension achievement, resulting in successful foreign language learning for higher education students. The interaction in collaborative concept mapping, lacking in individual concept mapping, has facilitated individual and group knowledge building. As a result, implementing this strategy may benefit both group and individual learning.